A phase II study of oral uracil/ftorafur (UFT®) plus leucovorin combined with oxaliplatin (TEGAFOX) as first-line treatment in patients with metastatic colorectal cancer - Bennouna, J; Perrier, H; Paillot, B; Priou, F; Jacob, J H; Hebbar, M; Bordenave, S; Seitz, J F; Cvitkovic, F; Dorval, E; Malek, K; Tonelli, D; et al. (British journal of cancer, 2006)
This phase II trial was performed to evaluate the efficacy and tolerability of a new combination of Uracil/Ftorafur (UFT ® )/leucovorin (LV) and oxaliplatin in patients (pts) with metastatic colorectal cancer (MCRC) who had not received prior chemotherapy for metastatic disease. Between February 2002 and October 2002, 64 patients received UFT ® 300 mg m −2 day −1 and LV 90 mg day −1 from day 1 to day 14 combined with oxaliplatin 130 mg m −2 on day 1, every 3 weeks. All patients were evaluable for safety analysis and 58 of 64 patients were eligible for efficacy. Responses were reviewed by an independent review committee. Of the 58 per-protocol defined assessable patients, 1 complete response and 20 partial responses were observed yielding a response rate of 34% (95% CI: 22–47). The median response duration was 8.74 months (range 1.6–14). The median time to progression and the median survival were 5.88 months (95% CI: 4.34–8.21) and 18.2 months (95% CI: 10–20.7), respectively. Diarrhoea and peripheral neuropathy were the most frequent and predictable toxicities. These events were reversible, noncumulative and manageable. Grade 3 diarrhoea occurred in only 11% of the patients. No grade 4 gastrointestinal toxicity was reported in the study. The incidence of grade 3/4 (National Cancer Institute Common Toxicity Criteria 2: NCI-CTC 2) peripheral neuropathy was 15%. Haematological toxicity was of mild to moderate intensity with 10% of the patients with Grade 3/4 neutropenia without any episode of complication. The TEGAFOX regimen, a new combination using UFT ® /LV and oxaliplatin every 3 weeks is feasible on an outpatient basis. The combination is safe and active and may offer a promising alternative to the intravenous route. Nevertheless this efficacy results should be confirmed by randomized phase III trials.